Successful ‘Kangaroo Mother Care’: A Necessity for Preterm Low Birth Weight Babies in Rural Hospital Settings in Bangladesh - Salam, Md Wasek; Hye, Mohammad Abdul; Kundu, Jayanta Kumar; Ahmed, Shuperna (Bangladesh Journal of Medical Science, 2022)
Kangaroo Mother Care (KMC) is a cost-effective solution in taking care of pre-term low birth weight neonates not only in developing countries with scarce resources, but also in developed countries with easy accessibility to technological advances like incubators. It provides an easy solution where the mother herself acts as an incubator and keeps the baby close to her in skinto- skin contact, and provides the baby the warmth, food, shelter and love that the baby needs to ensure its survival.In this paper we described the successful management of a preterm baby born at 29th gestational weeks weighing only 980 gm in a rural setting without any incubator and other technological equipment. The baby was in a critical condition since birth and despite adequate medical therapy she remained hypothermic. The KMC was initiated to keep her warm and marked improvements were noticed in the baby. The baby was discharged at day-14 with a body weight of 1100gm. Baby was in regular follow up and subsequently at 2-months 24days,she reached a desired body weight of 2100gm with improvement in feeding, movement and vital signs.It is concluded that, in a limited resource setting, KMC can act as a very effective measure in preventing neonatal morbidity by adequate heat regulation, exclusive breastfeeding and promoting early discharge from hospital. Bangladesh Journal of Medical Science Vol. 21 No. 04 October’22 Page : 875-882